Theorizing the Performative Effects of Penal Risk Technologies: (Re)producing the Subject Who Must Be Dangerous - Werth, Robert (Social & legal studies, 2019)
This article explores the ways in which practices of risk assessment exert material and semiotic effects that structure how penal subjects are constituted, imagined, and governed. In so doing, it proposes conceptual shifts in how we understand risk logics and practices. It contends that techniques of assessment and classification within parole operate performatively; that is, they do not so much describe reality as they constitute, structure and alter what they appear to report on. While this occurs through shaping the beliefs of penal actors – that is, through ideological mechanisms – this article focuses on the ways in which assessments exert institutional, bureaucratic and automatic effects independent of beliefs. I argue that, through exerting these effects, assessments make the risk of paroled subjects an institutional and practical certainty. While the dangerousness of individuals on parole is historically and ideologically contingent, contemporary practices of risk operate in a way that precludes the possibility of a non-dangerous individual.